The Political Economy of Digitalization and Climate Change Response in Nigeria - Ojakorotu, Victor; Olajide, Bamidele; Dunmade, Busola (International Journal of Criminology and Sociology, 2022)
Climate change is having serious impacts on the sustainability of the world. Growing scientific exactitude on causes and effects of climate change makes humanity’s response to it an urgent and critical need. Nigeria like many countries around the world is facing difficult times owing to the new environmental realities produced by the menace. Responding to climate change requires humanity’s best social, political, scientific, and technological efforts. To achieve this, this paper notes that digitalization can be a veritable climate change response tool in Nigeria. Dwelling on Schumpeter’s theory of innovation and the political economy approach, the paper argues that digitalization holds positives for Nigeria’s hitherto unimpressive climate change response but may not be practicable due to the social, economic and political contradictions that are producing unfavourable outcomes within the Nigerian state. This situation explains why mitigation and adaption efforts have not produced satisfactory results, a situation that puts citizens’ wellbeing in harm’s way in critical areas such as agriculture, housing, healthcare, and energy among others. The paper concludes that digitalization would make mitigation and adaptation wholesome and enhance the adequacy of climate change policies and programmes towards sustainable development in Nigeria. It then comes up with policy suggestions that can help mainstream digitalization as a tool for climate change response in the country.